2018
DOI: 10.1158/0008-5472.can-18-0757
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and Transposon Mutagenesis Identify Multiple Mechanisms of Resistance to the FGFR Inhibitor AZD4547

Abstract: In human cancers, FGFR signaling is frequently hyperactivated by deregulation of FGF ligands or by activating mutations in the FGFR receptors such as gene amplifications, point mutations, and gene fusions. As such, FGFR inhibitors are considered an attractive therapeutic strategy for patients with mutations in FGFR family members. We previously identified as a key driver of invasive lobular carcinoma (ILC) in an insertional mutagenesis screen using the transposon system. Here we explore whether these FGFR-driv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
3
30
1
Order By: Relevance
“…(23). Similarly, AZD4547 has been shown to be susceptible to acquired resistance (46). Data on acquired resistance with the newer inhibitors erdafitinib and pemigatinib (which have shown efficacy in patients with advanced cancers [17,20]) have yet to be reported.…”
Section: Futibatinib Was Associated With a Low Risk Of Drug Resistancmentioning
confidence: 99%
“…(23). Similarly, AZD4547 has been shown to be susceptible to acquired resistance (46). Data on acquired resistance with the newer inhibitors erdafitinib and pemigatinib (which have shown efficacy in patients with advanced cancers [17,20]) have yet to be reported.…”
Section: Futibatinib Was Associated With a Low Risk Of Drug Resistancmentioning
confidence: 99%
“…proliferation, drug treatment), cells with specific mutations conferring the ability to outcompete neighboring cells undergo clonal expansion, facilitating subsequent identification of these phenotype-driving mutations. This method has been used to select for specific phenotypes using ex vivo cell-based assays (15-17), as well as to drive the development of drug-resistant tumors in a engineered mouse models (18,19). However, previous ex vivo approaches using human cells have been limited by the relative inefficiency of delivering both transposon and transposase vectors to cells.…”
mentioning
confidence: 99%
“…A previous study has revealed that FGFR-2 mutation is an important driver of lung cancer, which has become a key target of lung cancer drug development. In an FGFR2-mutant resistant model, RASA1 was found to be inactivated ( 66 ).…”
Section: Rasa1 and Cancersmentioning
confidence: 99%
“…The activated Raf kinase continues to phosphorylate and activate MAPKK protein kinase MEK1/2 and finally phosphorylates and activates ERK1/2, inducing abnormal proliferation, invasion, growth, and distant metastasis of malignant tumours ( 75 , 123 ). In addition, loss of RASA1 function can enhance RAS-ERK signal amplification ( 66 , 78 ). PI3K/AKT have been described as key regulators of cell proliferation and differentiation and are involved in tumour cell proliferation, invasion, and metastasis ( 124 ).…”
Section: Potential Mechanism Of Rasa1 and Tumorigenesismentioning
confidence: 99%